High-temperature-resistant lithium ion battery electrode material and preparation method thereof
By combining modified nanocarbon fibers with ultrafine metal oxides and modified active materials with lithium cobalt oxides, combined with high-energy ball milling method and sol-gel method, the problem of unstable performance of traditional lithium-ion batteries at high temperatures is solved, and the high temperature tolerance and safety of the batteries are achieved.
Patent Information
- Application Number
- CN202510390256.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional lithium-ion batteries have problems such as electrolyte decomposition, electrode material expansion, capacity decay and thermal runaway in high-temperature environments, which limits their widespread use in high-temperature application scenarios.
The composite conductive material of modified nanocarbon fiber and ultrafine metal oxide is fully mixed by high-energy ball milling method, combined with the sol-gel method and high-temperature calcination process to synthesize the modified active material of lithium cobalt oxide and cobalt oxide, and prepare electrode materials through ultrasonic treatment and coating processes to ensure the thermal stability and cycling performance of the material at high temperature.
It significantly improves the high temperature resistance of lithium-ion batteries, ensures that the battery has long-term stability and safety in extreme high temperature environments, and is suitable for high temperature applications.
Smart Images

Figure CN119890316A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium battery technology, and in particular to a high temperature resistant lithium ion battery electrode material and a preparation method thereof. Background Art
[0002] With the advancement of science and technology and the development of new energy technologies, lithium-ion batteries are being used more and more widely in various fields. In particular, the demand for applications in high-temperature environments is gradually increasing, such as the long-term use of electric vehicles (EVs) in hot summers, the aerospace field, and high-temperature industrial equipment. These fields have put forward higher requirements for lithium-ion batteries, especially stability and safety in extreme high-temperature environments. Traditional lithium-ion batteries may have problems such as electrolyte decomposition, electrode material expansion, capacity decay, and thermal runaway at high temperatures, which limits their widespread application in these high-temperature application scenarios.
[0003] Most of the existing process technologies for lithium-ion battery electrode materials rely on conventional conductive materials and binders, such as traditional carbon black conductive materials and organic polymer binders. Although these materials exhibit good performance at room temperature, they often cannot maintain their stability under high temperature conditions. Traditional conductive materials are prone to oxidation or thermal degradation at high temperatures, resulting in decreased battery conductivity; while organic polymer binders are prone to decomposition at high temperatures, resulting in a weakened bonding strength between the electrode material and the current collector, thereby affecting the overall performance and safety of the battery. These shortcomings limit the reliability and long-term stability of existing batteries under high temperature conditions.
[0004] In view of this, it is necessary to improve the preparation process of lithium ion batteries in the prior art to solve the technical problem of insufficient high temperature resistance of lithium ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a high temperature resistant lithium ion battery electrode material and a preparation method thereof to solve the above technical problems.
[0006] To achieve this object, the present invention adopts the following technical solutions: A method for preparing a high temperature resistant lithium ion battery electrode material, comprising: Step S1, mixing the modified carbon nanofibers and ultrafine metal oxides in a preset ratio, and fully mixing them by high-energy ball milling to make them evenly distributed, to obtain a highly conductive composite conductive material; Step S2, mixing lithium cobalt oxide and cobalt oxide in a preset ratio, synthesizing them by a sol-gel method, and obtaining thermal stability and cycle performance at high temperature through a high-temperature calcination process, and obtaining a modified active material after crushing and screening; Step S3, mixing the conductive composite material, the active material, the inorganic binder and the polyimide plasticizer according to a preset mass ratio, adding an appropriate amount of an organic solvent, and performing ultrasonic treatment to uniformly disperse all the materials to obtain a uniform electrode slurry; Step S4, coating the prepared electrode slurry evenly on the surface of the metal current collector by a coating machine, and after coating, drying for a preset time to remove the solvent to obtain an electrode material; Step S5, placing the coated electrode material into a high-temperature oven for shaping treatment, setting the oven temperature to 150°C to 200°C, and maintaining a preset drying time to allow the binder and plasticizer to be completely stable at high temperature to obtain a finished electrode material.
[0007] Optionally, the ultrafine metal oxide is any one of the following: titanium oxide, zirconium oxide, aluminum oxide or magnesium oxide; Wherein, the mass ratio of the modified nano-carbon fiber to the ultrafine metal oxide is 1:0.1-0.3.
[0008] Optionally, the preparation process of the modified carbon nanofiber is: Step S101, mixing polyacrylonitrile fiber as a carbon fiber raw material with a swelling agent in a preset ratio, and stirring them fully to form a mixed raw material, so that the swelling agent is evenly distributed on the surface of the carbon fiber; Step S102, placing the mixed raw material under atmosphere protection and performing high temperature pretreatment, wherein the high temperature pretreatment temperature is 200° C. to 300° C. and the treatment time is 1 to 3 hours; Step S103, placing the pretreated carbon fiber into a reactor containing a catalyst, introducing a nitrogen atmosphere, raising the temperature to 700° C. to 900° C., and performing a pyrolysis treatment for 2 to 4 hours, so that the carbon fiber undergoes a pyrolysis reaction to form modified nanocarbon fibers; Step S104, after cooling, taking out the modified carbon nanofibers, cleaning the surface and removing impurities to obtain finished modified carbon nanofibers; Step S105, performing ultrasonic treatment on the modified carbon nanofiber product.
[0009] Optionally, the step S1 specifically includes: S11, using a surface modification method of solution impregnation, immersing the ultrafine metal oxide in deionized water, adding a surfactant for surface treatment, and then ultrasonically treating for 20-30 minutes; S12, placing the modified carbon nanofibers and the surface-treated ultrafine metal oxides into a grinding tank of a high-energy ball mill, and adding an appropriate amount of ball milling media according to the required material ratio; S13, starting the high-energy ball mill, and setting the grinding time, rotation speed and amplitude, and performing ball milling in the high-energy ball mill, so that the modified nano-carbon fibers and the ultrafine metal oxide particles are fully mixed and evenly distributed through the high-speed impact and friction of the ball milling medium; S14, after the ball milling is completed, the particle distribution of the composite conductive material of the modified nano-carbon fiber and the ultrafine metal oxide is checked by a particle size analyzer. If the particle size is uneven, the ball milling needs to be performed again for a short time; S15, placing the composite conductive material after high-energy ball milling in a vacuum drying oven, setting the drying temperature to 60° C. to 80° C., and performing a drying treatment for 12 hours; S16, after drying, the surface morphology of the composite conductive material is analyzed by electronic scanning equipment to check if there is no obvious particle agglomeration on the surface of the material.
[0010] Optionally, the step S2 specifically includes: S21, preparing high-purity lithium cobalt oxide and cobalt oxide raw materials, and mixing them in a mass ratio of 1:1 to 1:3; S22, adding a mixed raw material of lithium cobalt oxide and cobalt oxide to a solvent, then adding an appropriate amount of organic acid as a sol forming agent to allow the lithium cobalt oxide and cobalt oxide to be fully dissolved and evenly dispersed, then adding an appropriate amount of metal salt as a raw material, and controlling the pH value to keep the pH value of the reaction system between 3 and 5; S23, placing the mixed solution in a reaction container, using a stirrer to fully stir to ensure that the lithium cobalt oxide, the cobalt oxide and the metal salt are uniformly dissolved, heating the mixed solution to 60° C. to 80° C., and keeping stirring to gradually form a sol; S24, continue heating to 100°C to 120°C and keep the temperature stable, and perform drying treatment to make the sol form a gel.
[0011] Optionally, after step S24, the following steps may be further performed: S25, placing the dried gel material in a high-temperature furnace, introducing nitrogen or air as a protective gas, raising the temperature to 500° C. to 700° C., and performing a calcination treatment to obtain an active material; S26, after the calcination is completed, the heating is stopped and the active material is allowed to cool to room temperature in natural air, and the cooled active material is crushed by a grinder, and the particle size of the crushed particles is controlled within 20 microns; S27, screening the crushed active material through a sieve to remove impurities with oversized particles, screening powder with uniform particle size, and obtaining modified active material; wherein the mesh number of the sieve used in the screening process is 80 to 100 meshes.
[0012] Optionally, the step S3 specifically includes: S31, weighing solid components according to a preset mass ratio, and weighing the conductive composite material, the modified active material, the inorganic binder, and the polyimide plasticizer respectively; S32, placing the weighed solid component in a mixing container, and adding an appropriate amount of organic solvent for preliminary mixing to form a slurry, wherein the mass ratio of the solid component to the organic solvent is between 1:3 and 1:5; S33, slowly heating the preliminarily mixed slurry to 30°C to 40°C in a constant temperature water bath.
[0013] Optionally, after step S33, the following steps are further included: S34, before adding ultrasonic treatment, high-speed stirring at 600-800 rpm for 3-5 minutes is used for pretreatment to initially break up the initial agglomerates in the slurry; S35, transferring the pretreated slurry to an ultrasonic reaction device, using an ultrasonic frequency of 20-40 kHz and an output power of 300-500 W to continuously or intermittently treat the slurry for 30-60 minutes; S36, after the ultrasonic treatment is completed, the slurry is taken out and stirred at a low speed for 5 minutes, while the viscosity and fluidity of the slurry are tested to obtain a uniform electrode slurry.
[0014] Optionally, the step S4 specifically includes: S41, selecting copper foil or aluminum foil as a metal current collector, cleaning, degreasing and drying the surface thereof, and then preheating it in an oven to 50° C. to 80° C.; S42, using a coating machine, and pre-calibrating the coating machine, setting the coating knife gap, coating speed and pressure of the pressure roller; S43, transporting the prepared uniform electrode slurry to the feed tank of the coating machine through the pipeline system, and using a constant flow pump to maintain continuous and stable supply of the slurry; during the coating process, using a real-time monitoring system to monitor the coating thickness, and adjusting the coating parameters according to the monitored thickness data; S44, after coating, the metal current collector coated with the slurry is introduced into a preheating oven for preliminary pre-drying treatment, the oven temperature is set to 60°C to 80°C, and the treatment time is controlled to be 5 to 10 minutes.
[0015] The present invention also provides a high temperature resistant lithium ion battery electrode material, which is prepared by the above-mentioned preparation method of the high temperature resistant lithium ion battery electrode material, and the high temperature resistant lithium ion battery electrode material comprises: The conductive composite layer is composed of modified nano-carbon fibers and ultra-fine metal oxides, and is used to provide the conductivity and thermal stability of the electrode material; An active material layer, formed by synthesizing lithium cobalt oxide and cobalt oxide by a sol-gel method, for providing electrochemical activity of the battery; The bonding layer is composed of an inorganic binder and a polyimide plasticizer, and is used to improve the mechanical strength and stability of the electrode at high temperatures; The metal current collector is used to provide support and electron conduction functions, and aluminum foil or copper foil is selected.
[0016] Compared with the prior art, the present invention has the following beneficial effects: the modified nano-carbon fiber and the ultrafine metal oxide are fully mixed by a high-energy ball milling method to obtain a highly conductive composite conductive material, and then the modified active materials of lithium cobalt oxide and cobalt oxide are synthesized by a sol-gel method and a high-temperature calcination process to improve the thermal stability and cycle performance of the material at high temperatures; then, the conductive composite material, the active material, the inorganic binder and the polyimide plasticizer are mixed in a preset proportion, and an evenly dispersed electrode slurry is obtained by ultrasonic treatment, and the electrode slurry is evenly coated on the surface of the metal current collector by a coater, and the solvent is removed after a preset drying time, and after a shaping treatment, the stability and high-temperature tolerance of the electrode material are ensured to obtain a finished electrode material; the method combines an innovative combination of a new conductive composite material, an active material and a binder, significantly improves the high-temperature resistance of the battery, can ensure the long-term stability and safety of the battery in an extremely high-temperature environment, and is widely applicable to high-temperature applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0018] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.
[0019] Figure 1 This is one of the flow diagrams of the method for preparing the high temperature resistant lithium ion battery electrode material of the first embodiment; Figure 2 This is a second flow chart of the method for preparing the high temperature resistant lithium ion battery electrode material of the first embodiment; Figure 3This is the third flow chart of the method for preparing the high temperature resistant lithium ion battery electrode material of the first embodiment. DETAILED DESCRIPTION
[0020] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.
[0022] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0023] Embodiment 1: Combination Figures 1 to 3 As shown, an embodiment of the present invention provides a method for preparing a high temperature resistant lithium ion battery electrode material, comprising: Step S1, mixing the modified carbon nanofibers and ultrafine metal oxides in a preset ratio, and fully mixing them by high-energy ball milling to make them evenly distributed, to obtain a highly conductive composite conductive material; Step S2, mixing lithium cobalt oxide and cobalt oxide in a preset ratio, synthesizing them by a sol-gel method, and obtaining thermal stability and cycle performance at high temperature through a high-temperature calcination process, and obtaining a modified active material after crushing and screening; Step S3, mixing the conductive composite material, the active material, the inorganic binder and the polyimide plasticizer according to a preset mass ratio, adding an appropriate amount of an organic solvent, and performing ultrasonic treatment to uniformly disperse all the materials to obtain a uniform electrode slurry; Step S4, coating the prepared electrode slurry evenly on the surface of the metal current collector by a coating machine, and after coating, drying for a preset time to remove the solvent to obtain an electrode material; Step S5, placing the coated electrode material into a high-temperature oven for shaping treatment, setting the oven temperature to 150°C to 200°C, and maintaining a preset drying time to allow the binder and plasticizer to be completely stable at high temperature to obtain a finished electrode material.
[0024] The working principle of the present invention is as follows: the modified nano-carbon fiber and the ultrafine metal oxide are fully mixed by a high-energy ball milling method to obtain a highly conductive composite conductive material, and then the modified active materials of lithium cobalt oxide and cobalt oxide are synthesized by a sol-gel method and a high-temperature calcination process to improve the thermal stability and cycle performance of the material at high temperatures; then, the conductive composite material, the active material, the inorganic binder and the polyimide plasticizer are mixed in a preset proportion, and an evenly dispersed electrode slurry is obtained by ultrasonic treatment, and the electrode slurry is evenly coated on the surface of the metal current collector by a coater, and the solvent is removed after a preset drying time, and after a shaping treatment, the stability and high-temperature tolerance of the electrode material are ensured to obtain a finished electrode material; the method combines an innovative combination of a new conductive composite material, an active material and a binder, significantly improves the high-temperature resistance of the battery, can ensure the long-term stability and safety of the battery in an extremely high-temperature environment, and is widely applicable to high-temperature applications.
[0025] In this embodiment, it is specifically stated that the ultrafine metal oxide is any one of the following: titanium oxide, zirconium oxide, aluminum oxide or magnesium oxide; wherein the mass ratio of the modified nano-carbon fiber to the ultrafine metal oxide is 1:0.1-0.3.
[0026] In this embodiment, it is specifically described that the preparation process of the modified carbon nanofiber is: Step S101, mixing polyacrylonitrile fiber as a carbon fiber raw material with a swelling agent in a preset ratio, and stirring them fully to form a mixed raw material, so that the swelling agent is evenly distributed on the surface of the carbon fiber; Step S102, placing the mixed raw material under atmosphere protection and performing high temperature pretreatment, the high temperature pretreatment temperature is 200°C to 300°C, and the treatment time is 1 to 3 hours; to ensure that the expansion agent evenly penetrates and activates the carbon fiber; Step S103, placing the pretreated carbon fiber into a reactor containing a catalyst, introducing a nitrogen atmosphere, raising the temperature to 700° C. to 900° C., and performing a pyrolysis treatment for 2 to 4 hours, so that the carbon fiber undergoes a pyrolysis reaction to form modified nanocarbon fibers; Step S104, after cooling, taking out the modified carbon nanofibers, cleaning the surface and removing impurities to obtain finished modified carbon nanofibers; Step S105, ultrasonically treating the modified carbon nanofiber product to ensure uniform mixing with the ultrafine metal oxide in subsequent processes.
[0027] In this embodiment, it is specifically explained that step S1 specifically includes: S11, using a surface modification method of solution impregnation, immersing the ultrafine metal oxide in deionized water, adding a surfactant for surface treatment, and then ultrasonically treating for 20-30 minutes; In order to improve the adhesion between the modified nano-carbon fibers and the ultrafine metal oxides, the ultrafine metal oxides may be surface treated and then ultrasonically treated for 20-30 minutes to make their surfaces more hydrophilic and enhance their affinity with the modified nano-carbon fibers.
[0028] S12, placing the modified carbon nanofibers and the surface-treated ultrafine metal oxides into a grinding tank of a high-energy ball mill, and adding an appropriate amount of ball milling media according to the required material ratio; Ball milling media usually use steel balls or ceramic balls with a diameter of 5 mm to 10 mm to ensure that the two materials can be effectively dispersed and mixed evenly during the ball milling process.
[0029] S13, starting the high-energy ball mill, and setting the grinding time, rotation speed and amplitude, and performing ball milling in the high-energy ball mill, so that the modified nano-carbon fibers and the ultrafine metal oxide particles are fully mixed and evenly distributed through the high-speed impact and friction of the ball milling medium; Usually, the ball milling time is controlled between 1-3 hours, the speed is set at 500-1000 rpm, and the amplitude is 5-10 mm. In order to prevent excessive temperature from affecting material properties, the ball milling process needs to be stopped intermittently for cooling, and each stop time is 10-15 minutes.
[0030] During the ball milling process, the ratio of the ball milling media is critical to the final mixing effect. It is recommended to adjust the ratio of ball milling media to material before each ball milling, usually set to 5:1 to 10:1, to ensure sufficient stirring during ball milling and avoid excessive abrasion of the material.
[0031] S14, after the ball milling is completed, the particle distribution of the composite conductive material of the modified nano-carbon fiber and the ultrafine metal oxide is checked by a particle size analyzer. If the particle size is uneven, the ball milling needs to be performed again for a short time; Ensure that the particle size of the composite material is within the required range, usually less than 50 microns. If the particle size is uneven, it is necessary to perform ball milling again for a short time until the desired dispersion effect is achieved.
[0032] S15, placing the composite conductive material after high-energy ball milling in a vacuum drying oven, setting the drying temperature to 60° C. to 80° C., and performing a drying treatment for 12 hours; The purpose of this step is to remove any moisture that may be present to prevent it from adversely affecting subsequent processes and to ensure the long-term stability and conductivity of the material.
[0033] S16, after drying, performing surface morphology analysis on the composite conductive material by electronic scanning equipment to check if there is no obvious particle agglomeration on the surface of the material; Finally, the uniformly mixed modified nano-carbon fibers and ultrafine metal oxide composite conductive materials are collected and stored in a sealed container to prevent moisture or pollutants in the air from affecting their performance.
[0034] In this embodiment, it is specifically described that step S2 specifically includes: S21, preparing high-purity lithium cobalt oxide and cobalt oxide raw materials, and mixing them in a mass ratio of 1:1 to 1:3; First, prepare high-purity lithium cobalt oxide (LiCoO2) and cobalt oxide (Co3O4) raw materials. The purity of lithium cobalt oxide and cobalt oxide should reach more than 98% to ensure their stability and performance in subsequent reactions. According to the preset ratio, the two oxides are mixed in a mass ratio of 1:1 to 1:3 to adjust the structure and properties of the material so that it has excellent thermal stability and cycle performance at high temperatures.
[0035] S22, adding a mixed raw material of lithium cobalt oxide and cobalt oxide to a solvent, then adding an appropriate amount of organic acid as a sol forming agent to allow the lithium cobalt oxide and cobalt oxide to be fully dissolved and evenly dispersed, then adding an appropriate amount of metal salt as a raw material, and controlling the pH value to keep the pH value of the reaction system between 3 and 5; Deionized water is usually used as a solvent. Then, an appropriate amount of organic acid (such as acetic acid) is added as a sol-forming agent to ensure that lithium cobalt oxide and cobalt oxide can be fully dissolved and evenly dispersed. Next, an appropriate amount of metal salt (for example, cobalt chloride, lithium chloride) is added as a raw material, and the pH value of the reaction system is maintained between 3 and 5 by controlling the pH value to promote the formation of the sol.
[0036] S23, placing the mixed solution in a reaction container, using a stirrer to fully stir to ensure that the lithium cobalt oxide, the cobalt oxide and the metal salt are uniformly dissolved, heating the mixed solution to 60° C. to 80° C., and keeping stirring to gradually form a sol; During this process, the concentration of the sol should gradually increase and an obvious gelation phenomenon should appear. The formation of gel helps to improve the structural stability of the material.
[0037] S24, continue heating to 100°C to 120°C and keep the temperature stable, and perform drying treatment to make the sol form a gel.
[0038] The purpose of this step is to volatilize the water to make the sol form a gel. The drying time is generally 4 to 6 hours, until the gel becomes dry and no obvious water remains. At this point, the obtained gel material has a high specific surface area, which provides a good foundation for the subsequent high-temperature calcination process.
[0039] In this embodiment, it is specifically explained that after step S24, the following steps are further included: S25, placing the dried gel material in a high temperature furnace, introducing nitrogen or air as a protective gas, raising the temperature to 500°C to 700°C, and calcining to obtain an active material; the calcination time is generally 3 to 5 hours, and the selection of the calcination temperature directly affects the crystal structure and activity of the lithium cobalt oxide and the cobalt oxide. Through the calcination process, the lithium cobalt oxide and the cobalt oxide are fully reacted at high temperature to form an active material with excellent thermal stability and cycle performance.
[0040] S26, after the calcination is completed, the heating is stopped and the active material is allowed to cool to room temperature in natural air, and the cooled active material is crushed by a grinder, and the particle size of the crushed particles is controlled within 20 microns; The purpose of crushing is to make the material particles finer for subsequent applications. The particle size of the crushed particles is controlled within 20 microns to ensure their uniform distribution and improve the conductivity of the material.
[0041] S27, sieving the crushed active material through a sieve to remove impurities with oversized particles, sieving powder with uniform particle size, and obtaining modified active material; wherein the mesh number of the sieve used in the sieving process is 80 to 100 meshes; to ensure the uniformity of the material particles. The uniformity of particle size distribution is crucial to the performance of subsequent electrode materials, ensuring that the active material has good conductivity and thermal stability.
[0042] The modified active material obtained by screening is stored in a sealed container to prevent moisture in the air from affecting its stability. During storage, the container should be kept dry to prevent the material from absorbing moisture. This material will be used in the subsequent preparation of electrode slurry as the active ingredient of the electrode.
[0043] In this embodiment, it is specifically described that step S3 specifically includes: S31, weighing solid components according to a preset mass ratio, and weighing the conductive composite material, the modified active material, the inorganic binder, and the polyimide plasticizer respectively; Typically, the mass ratio of the components can be controlled at 2:7:0.5:0.3 (this ratio can be adjusted within a reasonable range according to specific application requirements) of conductive composite material: active material: inorganic binder: polyimide plasticizer to ensure that the subsequent slurry has optimal electrochemical performance and mechanical stability.
[0044] S32, placing the weighed solid component in a mixing container, and adding an appropriate amount of organic solvent for preliminary mixing to form a slurry, wherein the mass ratio of the solid component to the organic solvent is between 1:3 and 1:5; The organic solvent is preferably N-methylpyrrolidone (NMP) or dimethylformamide (DMF). To ensure that the solid content of the slurry is between 10% and 20%, the mass ratio of solid to solvent can be controlled to be 1:3 to 1:5. In this step, a magnetic stirrer or a mechanical stirrer is used to perform preliminary stirring at a medium speed (e.g., 300-500 rpm) for 5-10 minutes to ensure uniform contact of the components.
[0045] S33, slowly heating the preliminarily mixed slurry to 30°C to 40°C in a constant temperature water bath. This step helps to reduce the viscosity of the organic solvent, thereby improving the dispersion effect of the solid components and promoting the uniformity of the subsequent ultrasonic treatment. During this period, stirring is continued at a low speed to ensure uniform temperature distribution.
[0046] S34, before adding ultrasonic treatment, high-speed stirring at 600-800 rpm for 3-5 minutes is used for pretreatment to initially break up the initial agglomerates in the slurry; S35, transferring the pretreated slurry to an ultrasonic reaction device, using an ultrasonic frequency of 20-40 kHz and an output power of 300-500 W to continuously or intermittently treat the slurry for 30-60 minutes; In order to avoid affecting the material properties due to excessive local temperature during the ultrasonic process, a 5-minute working and 2-minute stopping cycle mode can be adopted to ensure that the slurry temperature is kept below 40°C during the ultrasonic treatment. This step allows the conductive composite material, active material, inorganic binder and polyimide plasticizer to be fully dispersed and evenly mixed.
[0047] S36, after the ultrasonic treatment is completed, the slurry is taken out and stirred at a low speed for 5 minutes, while the viscosity and fluidity of the slurry are tested to obtain a uniform electrode slurry.
[0048] If the slurry viscosity is found to be too high or the solid dispersion is uneven, a small amount of organic solvent can be added and ultrasonic treatment can be performed again for a short time (5-10 minutes) until the slurry reaches the expected fluidity and uniformity requirements.
[0049] Take a sample of the electrode slurry and use a particle size analyzer or optical microscope to observe the dispersion state of the solid particles to ensure that there is no obvious agglomeration of the components and that the particles are evenly distributed. If necessary, adjust the processing parameters or add solvent until the test results meet the requirements of the electrode coating process.
[0050] The final uniform electrode slurry is transferred to a sealed, solvent-resistant container to prevent organic solvent volatilization and external contamination, providing a stable and uniform slurry raw material for the subsequent coating process in step S4.
[0051] In this embodiment, it is specifically described that step S4 specifically includes: S41, select copper foil or aluminum foil as the metal current collector, clean, degrease and dry its surface to ensure that the surface is dust-free and oil-free; then preheat it in an oven to 50°C to 80°C to improve the adhesion and spreadability of the electrode slurry on the current collector.
[0052] S42, use a coater (such as a slot coater or a blade coater), and pre-calibrate the coater, set the coating knife gap, coating speed and roller pressure; generally set the coating thickness to 20-40 microns, the coating speed to 5-10 m / min, and the roller pressure to ensure that the slurry is evenly spread without edge running, meeting the process requirements.
[0053] S43, transporting the prepared uniform electrode slurry to the feed tank of the coating machine through the pipeline system, and using a constant flow pump to maintain continuous and stable supply of the slurry; during the coating process, using a real-time monitoring system (such as a laser displacement sensor) to monitor the coating thickness, and adjusting the coating parameters based on the monitored thickness data; ensuring that the slurry is evenly covered on the surface of the metal current collector.
[0054] S44, after coating, the metal current collector coated with the slurry is introduced into a preheating oven for preliminary pre-drying treatment, the oven temperature is set to 60°C to 80°C, and the treatment time is controlled to be 5 to 10 minutes; The main purpose is to quickly remove the surface solvent, prevent the slurry from sagging and uneven film formation, and at the same time form a preliminary stable coating structure.
[0055] Embodiment 2: The present invention also provides a high temperature resistant lithium ion battery electrode material, which is prepared by the above method for preparing the high temperature resistant lithium ion battery electrode material. The high temperature resistant lithium ion battery electrode material comprises: The conductive composite layer is composed of modified nano-carbon fibers and ultra-fine metal oxides and is used to provide the conductivity and thermal stability of the electrode material.
[0056] The active material layer is formed by synthesizing lithium cobalt oxide and cobalt oxide through a sol-gel method, and is used to provide electrochemical activity of the battery.
[0057] The bonding layer is composed of an inorganic binder and a polyimide plasticizer and is used to improve the mechanical strength and stability of the electrode at high temperatures.
[0058] The metal current collector is used to provide support and electron conduction functions, and aluminum foil or copper foil is selected.
[0059] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high temperature resistant lithium ion battery electrode material, characterized in that: include: Step S1, mixing the modified carbon nanofibers and ultrafine metal oxides in a preset ratio, and fully mixing them by high-energy ball milling to make them evenly distributed, to obtain a highly conductive composite conductive material; Step S2, mixing lithium cobalt oxide and cobalt oxide in a preset ratio, synthesizing them by a sol-gel method, and obtaining thermal stability and cycle performance at high temperature through a high-temperature calcination process, and obtaining a modified active material after crushing and screening; Step S3, mixing the conductive composite material, the active material, the inorganic binder and the polyimide plasticizer according to a preset mass ratio, adding an appropriate amount of an organic solvent, and performing ultrasonic treatment to uniformly disperse all the materials to obtain a uniform electrode slurry; Step S4, coating the prepared electrode slurry evenly on the surface of the metal current collector by a coating machine, and after coating, drying for a preset time to remove the solvent to obtain an electrode material; Step S5, placing the coated electrode material into a high-temperature oven for shaping treatment, setting the oven temperature to 150°C to 200°C, and maintaining a preset drying time to allow the binder and plasticizer to be completely stable at high temperature to obtain a finished electrode material.
2. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The ultrafine metal oxide is any one of the following: titanium oxide, zirconium oxide, aluminum oxide or magnesium oxide; Wherein, the mass ratio of the modified nano-carbon fiber to the ultrafine metal oxide is 1:0.1-0.
3.
3. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The preparation process of the modified carbon nanofiber is as follows: Step S101, mixing polyacrylonitrile fiber as a carbon fiber raw material with a swelling agent in a preset ratio, and stirring them fully to form a mixed raw material, so that the swelling agent is evenly distributed on the surface of the carbon fiber; Step S102, placing the mixed raw material under atmosphere protection and performing high temperature pretreatment, wherein the high temperature pretreatment temperature is 200° C. to 300° C. and the treatment time is 1 to 3 hours; Step S103, placing the pretreated carbon fiber into a reactor containing a catalyst, introducing a nitrogen atmosphere, raising the temperature to 700° C. to 900° C., and performing a pyrolysis treatment for 2 to 4 hours, so that the carbon fiber undergoes a pyrolysis reaction to form modified nanocarbon fibers; Step S104, after cooling, taking out the modified carbon nanofibers, cleaning the surface and removing impurities to obtain finished modified carbon nanofibers; Step S105, performing ultrasonic treatment on the modified carbon nanofiber product.
4. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The step S1 specifically includes: S11, using a surface modification method of solution impregnation, immersing the ultrafine metal oxide in deionized water, adding a surfactant for surface treatment, and then ultrasonically treating for 20-30 minutes; S12, placing the modified carbon nanofibers and the surface-treated ultrafine metal oxides into a grinding tank of a high-energy ball mill, and adding an appropriate amount of ball milling media according to the required material ratio; S13, starting the high-energy ball mill, and setting the grinding time, rotation speed and amplitude, and performing ball milling in the high-energy ball mill, so that the modified nano-carbon fibers and the ultrafine metal oxide particles are fully mixed and evenly distributed through the high-speed impact and friction of the ball milling medium; S14, after the ball milling is completed, the particle distribution of the composite conductive material of the modified nano-carbon fiber and the ultrafine metal oxide is checked by a particle size analyzer. If the particle size is uneven, the ball milling needs to be performed again for a short time; S15, placing the composite conductive material after high-energy ball milling in a vacuum drying oven, setting the drying temperature to 60° C. to 80° C., and performing a drying treatment for 12 hours; S16, after drying, the surface morphology of the composite conductive material is analyzed by electronic scanning equipment to check if there is no obvious particle agglomeration on the surface of the material.
5. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The step S2 specifically includes: S21, preparing high-purity lithium cobalt oxide and cobalt oxide raw materials, and mixing them in a mass ratio of 1:1 to 1:3; S22, adding a mixed raw material of lithium cobalt oxide and cobalt oxide to a solvent, then adding an appropriate amount of organic acid as a sol forming agent to allow the lithium cobalt oxide and cobalt oxide to be fully dissolved and evenly dispersed, then adding an appropriate amount of metal salt as a raw material, and controlling the pH value to keep the pH value of the reaction system between 3 and 5; S23, placing the mixed solution in a reaction container, using a stirrer to fully stir to ensure that the lithium cobalt oxide, the cobalt oxide and the metal salt are uniformly dissolved, heating the mixed solution to 60° C. to 80° C., and keeping stirring to gradually form a sol; S24, continue heating to 100°C to 120°C and keep the temperature stable, and perform drying treatment to make the sol form a gel.
6. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 5, characterized in that: After step S24, the following steps are also included: S25, placing the dried gel material in a high-temperature furnace, introducing nitrogen or air as a protective gas, raising the temperature to 500° C. to 700° C., and performing a calcination treatment to obtain an active material; S26, after the calcination is completed, the heating is stopped and the active material is allowed to cool to room temperature in natural air, and the cooled active material is crushed by a grinder, and the particle size of the crushed particles is controlled within 20 microns; S27, screening the crushed active material through a sieve to remove impurities with oversized particles, screening powder with uniform particle size, and obtaining modified active material; wherein the mesh number of the sieve used in the screening process is 80 to 100 meshes.
7. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The step S3 specifically includes: S31, weighing solid components according to a preset mass ratio, and weighing the conductive composite material, the modified active material, the inorganic binder, and the polyimide plasticizer respectively; S32, placing the weighed solid component in a mixing container, and adding an appropriate amount of organic solvent for preliminary mixing to form a slurry, wherein the mass ratio of the solid component to the organic solvent is between 1:3 and 1:5; S33, slowly heating the preliminarily mixed slurry to 30°C to 40°C in a constant temperature water bath.
8. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 7, characterized in that: After step S33, the following steps are also included: S34, before adding ultrasonic treatment, high-speed stirring at 600-800 rpm for 3-5 minutes is used for pretreatment to initially break up the initial agglomerates in the slurry; S35, transferring the pretreated slurry to an ultrasonic reaction device, using an ultrasonic frequency of 20-40 kHz and an output power of 300-500 W to continuously or intermittently treat the slurry for 30-60 minutes; S36, after the ultrasonic treatment is completed, the slurry is taken out and stirred at a low speed for 5 minutes, while the viscosity and fluidity of the slurry are tested to obtain a uniform electrode slurry.
9. The method for preparing a high temperature resistant lithium ion battery electrode material according to claim 1, characterized in that: The step S4 specifically includes: S41, selecting copper foil or aluminum foil as a metal current collector, cleaning, degreasing and drying the surface thereof, and then preheating in an oven to 50° C. to 80° C.; S42, using a coating machine, and pre-calibrating the coating machine, setting the coating knife gap, coating speed and pressure of the pressure roller; S43, transporting the prepared uniform electrode slurry to the feed tank of the coating machine through the pipeline system, and using a constant flow pump to maintain continuous and stable supply of the slurry; during the coating process, using a real-time monitoring system to monitor the coating thickness, and adjusting the coating parameters according to the monitored thickness data; S44, after coating, the metal current collector coated with the slurry is introduced into a preheating oven for preliminary pre-drying treatment, the oven temperature is set to 60°C to 80°C, and the treatment time is controlled to be 5 to 10 minutes.
10. A high temperature resistant lithium ion battery electrode material, characterized in that: The high temperature resistant lithium ion battery electrode material is prepared by the preparation method of any one of claims 1 to 9, wherein the high temperature resistant lithium ion battery electrode material comprises: The conductive composite layer is composed of modified nano-carbon fibers and ultra-fine metal oxides, and is used to provide the conductivity and thermal stability of the electrode material; An active material layer, formed by synthesizing lithium cobalt oxide and cobalt oxide by a sol-gel method, for providing electrochemical activity of the battery; The bonding layer is composed of an inorganic binder and a polyimide plasticizer and is used to improve the mechanical strength and stability of the electrode at high temperatures; The metal current collector is used to provide support and electron conduction functions, and aluminum foil or copper foil is selected.
Citation Information
Patent Citations
A novel graphene conductive agent for a lithium ion battery and a preparation method thereof
CN109119634A
Binder for lithium ion batteries and electrode and separator using same
CN111164807A
Binder for lithium ion battery, and electrode and separator using same
CN117986620A
Electrode plate and battery
CN118867244A
High-temperature-resistant polymer lithium battery composition and preparation method thereof
CN119230920A